Recurrent pericarditis in children and adolescents: a multicentre cohort study. Issue 9 (September 2016) - Imazio, Massimo; Brucato, Antonio; Pluymaekers, Nikki; Breda, Luciana; Calabri, Giovanni; Cantarini, Luca; Cimaz, Rolando; Colimodio, Filomena; Corona, Fabrizia; Cumetti, Davide; Cuccio, Chiara Di Blasi Lo; Gattorno, Marco; et al.
Abstract : Objective: Limited data are available about recurrent pericarditis in children. We sought to explore contemporary causes, characteristics, therapies and outcomes of recurrent pericarditis in paediatric patients. Methods: A multicentre (eight sites) cohort study of 110 consecutive cases of paediatric patients with at least two recurrences of pericarditis over an 11-year period (2000–2010) [median 13 years, interquartile range (IQR) 5, 69 boys]. Results: Recurrences were idiopathic or viral in 89.1% of cases, followed by postpericardiotomy syndrome (9.1%) and familial Mediterranean fever (0.9%). Recurrent pericarditis was treated with nonsteroidal anti-inflammatory drugs (NSAIDs) in 80.9% of cases, corticosteroids in 64.8% and colchicine was added in 61.8%. Immunosuppressive therapies were administered in 15.5% of patients after subsequent recurrences. After a median follow-up of 60th months, 528 subsequent recurrences were recorded (median 3, range 2–25). Corticosteroid-treated patients experienced more recurrences (standardized risk of recurrence per 100 person-years was 93.2 for patients treated with corticosteroids and 45.2 for those without), side effects and disease-related hospitalizations (for all P < 0.05). Adjuvant therapy with colchicine was associated with a decrease in the risk of recurrence from 3.74 per year before initiation of colchicine to 1.37 per year after ( P < 0.05). Anakinra therapy (n = 12) was associated with a drop in the number of recurrences from 4.29 per year before to 0.14 per year after ( P < 0.05). Transient constrictive pericarditis developed in 2.7% of patients. Conclusion: Recurrent pericarditis has an overall favourable prognosis in children, although it may require frequent readmissions and seriously affect the quality of life, especially in patients treated with corticosteroids. Colchicine or anakinra therapies were associated with significant decrease in the risk of recurrence.